Moraxella nonliquefaciens septic arthritis in a hematopoietic stem cell transplant patient a case report and review of the literature. Issue 3 (May 2019) - Khalife, Mohamad; Merashli, Mira; Kanj, Souha S.
Abstract: Background: Septic arthritis is a common rheumatologic condition with myriad microbiological causative agents. Moraxella is one of the very rare causes of septic arthritis. We hereby present the third case of Moraxella nonliquefaciens septic arthritis and the first case in a hematopoietic stem cell transplant patient (HSCT) along with a brief review of the literature. Methods: We used PubMed with google search engine to search the literature for reported cases of moraxella septic arthritis. Results: Information on 19 other cases of moraxella infectious arthritis was found. M. catarrhalis was the most common species isolated. Only 2 reports on M. nonliquefaciens were found; the first one in a multiple myeloma patient and the second one in a diabetic patient on hemodialysis. Predisposing conditions included inflammatory arthritis, prosthetic joints, diabetes, Human Immunodeficiency Virus (HIV) infection, Hepatitis C, hemodialysis, esophageal cancer, valve replacements, alcoholism and Intravenous (IV) drug use. The age group of the reported cases ranged from 3 months to 78 years. Conclusion: Infectious arthritis with Moraxella spp. is a very rare entity which can occur in any age group and in the setting of various underlying medical conditions.